Judgment of blame in teenagers with Asperger's syndrome. (2nd July 2016) - Salvano-Pardieu, Véronique; Blanc, Romuald; Combalbert, Nicolas; Pierratte, Aurélia; Manktelow, Ken; Maintier, Christine; Lepeltier, Sandra; Gimenes, Guillaume; Barthelemy, Catherine; Fontaine, Roger
ABSTRACT: The judgment of blame was studied in a group of 28 teenagers, 14 with Asperger syndrome (AS) and 14 typically developed. Teenagers in each group were matched by age, cognitive development and academic level. They were presented with 12 short vignettes in which they had to judge an action according to the intent of the actor (deliberate and accidental), the consequences of the action (presence and absence) and the seriousness of the situation (low, medium and high). Results showed a significant difference in the patterns of judgment of both groups. The AS group judged the action according to the physical consequence of the action more than the intent of the actor; the opposite was observed with the control group. In addition, the AS teenagers were less capable than the control group of grading injury to a person when apportioning blame especially when they were not familiar with the social situations. This result suggests that the judgement of the seriousness of the outcome of the social interaction is linked with its level of familiarity. Furthermore, result are congruent with the assumption that two different cognitive structures, deontic reasoning and perspective taking, are involved in the judgment of blame.